Diurnal physiological response of tomato cultivation to the application of silicon under salinity conditions - López-Cuén, Pedro Iván; González-Mendoza, Daniel; Escobosa-García, María Isabel; Cárdenas Salazar, Víctor; Núñez-Ramírez, Fidel; Soto-Ortíz, Roberto; Ruiz-Alvarado, Cristina (Revista Mexicana de Ciencias Agrícolas, 2020)
Silicon (Si) has beneficial effects on the tolerance of plants to various biotic and abiotic stresses. The objective of this study was to determine the effect of Si nutrition in tomato grown under conditions of induced saline stress (S), on leaf temperature, chlorophyll fluorescence and stomatal conductance (gs). The experiment was conducted under greenhouse conditions during the spring-summer 2017 cycle. A randomized distributed plot design was used. In which the main plot was salinity [with NaCl or with standard nutrient solution (SNS)] and the subplot was the application of Si (0, 4, 8 g L-1). The variables were measured during the day. The results showed that the leaf temperature increased at dawn in plants with NaCl and at sunset the effect was reversed and the highest values were in plants with SNS. At noon, Si × S interaction was identified in the photosynthetic efficiency (Fv/Fm) and minimal fluorescence (Fo) variables. The maximum fluorescence (Fm) was more affected by the type of salinity, with the highest values of plants with SNS. It was concluded that the diurnal physiological response of the tomato plant grown under saline conditions, will depend on the type of salt used and the dose of Si, especially at early and late hours of the day.
Keywords: greenhouse; mineral nutrition; plant physiology; saline stress; sodium chloride